2003
DOI: 10.1016/s0040-9383(02)00012-5
|View full text |Cite
|
Sign up to set email alerts
|

Infinite families of links with trivial Jones polynomial

Abstract: For each k ¿ 2, we exhibit inÿnite families of prime k-component links with Jones polynomial equal to that of the k-component unlink.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 11 publications
2
54
0
Order By: Relevance
“…This link, L and the corresponding link L s with a switched crossing have the property that both L and L s have the same Jones polynomial as an unlink of two components. These link diagrams were constructed using the methods of [19].…”
Section: Undetectable Examplesmentioning
confidence: 99%
“…This link, L and the corresponding link L s with a switched crossing have the property that both L and L s have the same Jones polynomial as an unlink of two components. These link diagrams were constructed using the methods of [19].…”
Section: Undetectable Examplesmentioning
confidence: 99%
“…Note that C is an untwisted double of the core of V 2 . By Propositions 2.3 and 2.4 of [EKT03], L = k ∪ C is a prime link. Let K q denote the knot obtained from k by 1/q-surgery on the trivial knot C. We take q > 0 for simplicity.…”
mentioning
confidence: 96%
“…In fact, there are certain class of links with trivial Jones' polynomial [28]. We checked some examples of links sharing the same Jones' polynomial but different colored Jones and observed that the Rényi entropies are different.…”
Section: Jhep02(2018)163 5 Conclusion and Discussionmentioning
confidence: 99%